2022
DOI: 10.3389/fonc.2022.1034519
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics nomogram for prediction of microvascular invasion in hepatocellular carcinoma based on MR imaging with Gd-EOB-DTPA

Abstract: ObjectiveTo develop a radiomics nomogram for predicting microvascular invasion (MVI) before surgery in hepatocellular carcinoma (HCC) patients.Materials and MethodsThe data from a total of 189 HCC patients (training cohort: n = 141; validation cohort: n = 48) were collected, involving the clinical data and imaging characteristics. Radiomics features of all patients were extracted from hepatobiliary phase (HBP) in 15 min. Least absolute shrinkage selection operator (LASSO) regression and logistic regression wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Nomograms combining clinical risk factors and the radiomics score have been widely used to solve practical clinical problems. Our findings are consistent with many previous studies showing that the combination of clinical risk factors and radiomics improves a model's performance, producing robust results [59][60][61][62]. In this study, a clinical-radiomics nomogram was constructed by integrating age, CEUS-reported ETE, BMUS Radscore, and CEUS Radscore.…”
Section: Discussionsupporting
confidence: 90%
“…Nomograms combining clinical risk factors and the radiomics score have been widely used to solve practical clinical problems. Our findings are consistent with many previous studies showing that the combination of clinical risk factors and radiomics improves a model's performance, producing robust results [59][60][61][62]. In this study, a clinical-radiomics nomogram was constructed by integrating age, CEUS-reported ETE, BMUS Radscore, and CEUS Radscore.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, nomogram models capable of preoperatively predicting MVI-positivity and its M2 classification in patients with HCC were developed. These models incorporated both clinical variables and preoperative MRI features, and demonstrated strong performance in predicting MVI status, with AUC values ranging between 0.700 and 0.920, consistent with previous findings (19,21,22). A notable advantage of the present nomogram model is its reliance on relatively simple and easily obtainable clinical parameters and MRI features.…”
Section: Discussionsupporting
confidence: 86%
“…Xu et al (25) reported no notable disparity in early recurrence after curative resection between patients with M0 HCC and patients with M1 HCC; however, the M2 grade was potentially associated with a poorer prognosis in patients with HCC. Although numerous studies (6,7,19,21,22,(26)(27)(28) have focused on predicting MVI status in patients with HCC, few have explored the preoperative grading of M2. To the best of our knowledge, no previous attempts have been made to use clinical and MRI features for preoperative prediction of the M2 classification in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation